Lives Made from Detritus: The Commercialization of Canine Excreta by the Plebian Groups During Mexico City’s Massacres of Vagabond Dogs, 1779-1821 - Luna Loranca, Arturo (2022)
In the late eighteenth and early nineteenth century, the authorities of Mexico City carried out a series of slaughters of so-called vagabond dogs (strays), which claimed the lives of 20,000 to 30,000 canines. The sacrifice of these animals was not well-received by certain sectors of society. This article argues that studying the material relationships established between dogs and plebian groups can partly help explain the reluctance demonstrated by the residents of Mexico City towards the slaughters. Its central argument is that plebian groups did not share the same view as colonial authorities of dogs. While authorities regarded dogs as a latent danger, plebian groups saw dogs as producers of a monetizable good: excreta. Some economic sectors, such as the medical marketplace and leather tanneries, had a high demand for dog excrement.